Racism and discrimination in healthcare: what role for bioethics? (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The objective of this paper is twofold. Firstly, the different forms of racism and discrimination in healthcare are explored and framed in a three-level analysis which includes practices, policies, and knowledge. Secondly, the paper translates such analysis into the current bioethics debates to provide an overview of the possible tools and strategies bioethics can put in place to mitigate and contrast racism and discrimination in healthcare. This is meant to stimulate a higher awareness among the bioethics community about the role that we as scholars and our discipline as a field of knowledge can play in fighting racism and discrimination in healthcare, which in turn is fundamental to contribute to more just, inclusive and equitable healthcare systems and societies.
Keywords: racism and discrimination; social justice; race; genomics; healthcare inequalities